Maternal Oral Health and Early Childhood Caries amongst Low-Income Families (2020)
Objective: To determine the association between maternal oral health and ECC and explore the role of maternal and child behaviours in explaining this association. Basic research design: A cross-sectional survey. Clinical setting: Public Healthcare Services in Pasto, Colombia. Participants: 384 mothers and their 2-5-year-old children. Main outcome measures: Mothers completed a questionnaire to provide information on sociodemographic and behavioural factors and were examined for caries experience (DMFS index) and periodontal status (Community Periodontal Index). Children were examined for dental caries (dmfs index). The association between maternal dental indicators and child dmfs was assessed in negative binomial regression models adjusting for confounders. Results: About 96% and 33% of mothers had caries experience and periodontal disease, respectively. The mean dmfs was 7.4 (SD: 9.5, range: 0-71). Maternal DMFS, but not the CPI index, was positively associated with children’s dmfs (Rate Ratio: 2.51, 95%CI: 1.59-3.97) after adjustments for sociodemographic and behavioural factors. Conclusions: Maternal caries experience, but not their periodontal status, was positively associated with ECC in their children. Maternal and child behaviours explained little of this association.